Basic Provisions and Requirements for the Formation of Interior Spaces of Hotels - Nilufar, Mannopova; Farrukhovna, Israilova Nigina (European Journal of Life Safety and Stability (2660-9630), 2021)
When creating a hotel, today an important issue is the design of its interior and exterior, therefore, consumer preferences should be taken into account.